Modem Recognition Algorithm for Software Defined Radio Base Station - Rukumangatha Rajah, Sivaraman (2004)
Mobile communications industry continuously evolves the wireless standards from 2G to 2.5G, 3G and then further onto 4G. Each generation differs significantly in link layer and physical layer protocol standards causing problems to subscribers, network operators and equipment vendors. The root cause of the problem is that the current hardware is not flexible enough to support future communication systems. To address this issue, Software Defined Radio (SDR) plays an important role to bridge the hardware limitation.